Roles of bone-derived hormones in type 2 diabetes and cardiovascular pathophysiology - Xuzhu Lin; Danise-Ann Onda; Chieh-Hsin Yang; Joshua R. Lewis; Itamar Levinger; Kim Loh (Elsevier, 2020)
Background: Emerging evidence demonstrates that bone is an endocrine organ capable of influencing multiple physiological and pathological processes through the secretion of hormones. Recent research suggests complex crosstalk between the bone and other metabolic and cardiovascular tissues. It was uncovered that three of these bone-derived hormones-osteocalcin, lipocalin 2, and sclerostin-are involved in the endocrine regulations of cardiometabolic health and play vital roles in the pathophysiological process of developing cardiometabolic syndromes such as type 2 diabetes and cardiovascular disease. Chronic low-grade inflammation is one of the hallmarks of cardiometabolic diseases and a major contributor to disease progression. Novel evidence also implicates important roles of bone-derived hormones in the regulation of chronic inflammation. Scope of review: In this review, we provide a detailed overview of the physiological and pathological roles of osteocalcin, lipocalin 2, and sclerostin in cardiometabolic health regulation and disease development, with a focus on the modulation of chronic inflammation. Major conclusions: Evidence supports that osteocalcin has a protective role in cardiometabolic health, and an increase of lipocalin 2 contributes to the development of cardiometabolic diseases partly via pro-inflammatory effects. The roles of sclerostin appear to be complicated: It exerts pro-adiposity and pro-insulin resistance effects in type 2 diabetes and has an anti-calcification effect during cardiovascular disease. A better understanding of the actions of these bone-derived hormones in the pathophysiology of cardiometabolic diseases will provide crucial insights to help further research develop new therapeutic strategies to treat these diseases.